Severe megaloblastic anemia in twin pregnancy mimicking partial hemolysis, elevated liver enzymes and low platelet count syndrome: a case report - Singh, S. Momon; Thakur, Vaidehi; Singh, P. Manisana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Vitamin B12 is well known cause of megaloblastic anemia. However, it is uncommon in pregnancy, occurs in 10-28% of uncomplicated pregnancies, and is associated with few complications. Present case of 32 years old woman with twin-pregnancy at late gestation who was diagnosed with severe anemia in a local private clinic. On arrival to medical center, lab findings together with her clinical picture warranted the concern for differential diagnosis of partial hemolysis, elevated liver enzymes and low platelet count (HELLP), but later it was found to be a case of vitamin B12 deficiency since additional lab findings. Blood transfusions were given, and patient responded well to B12 supplementation. Pregnancy was carried to term and delivered twin live babies but otherwise well at birth and had normal developmental milestones thereafter. Our case emphasizes the importance of screening for B12 deficiency in pregnancy, especially in at-risk women (twin-pregnancy in pure vegetarian women) with unexplained anemia/r thrombocytopenia.